2010
DOI: 10.1590/s0102-86502010000500007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between two techniques of incisional hernia repair with polypropylene mesh in rabbits

Abstract: Purpose:To compare two different incisional hernia repair techniques (repair with a polypropylene mesh reinforcement on the peritonium-aponeurosis versus polypropylene mesh sutured to the borders of the hernial ring as a bridge) in rabbits. Methods: Incisional hernia was experimentally developed through a 4-cm median incision in 60 rabbits. After 30 days, half of the animals were operated for primary wall closure and placement of a polypropylene mesh reinforcement, while the other half had a polypropylene mesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In a recent study conducted in our laboratory, we observed a significant reduction in the mechanical strength of ileum and colon rat anastomosis using an experimental model of chronic diabetes, with similar characteristics to the one used in this study 7,8 .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In a recent study conducted in our laboratory, we observed a significant reduction in the mechanical strength of ileum and colon rat anastomosis using an experimental model of chronic diabetes, with similar characteristics to the one used in this study 7,8 .…”
Section: Discussionsupporting
confidence: 74%
“…However, diabetes can also impair the healing of surgical wounds by causing delay in the migration of leukocytes and macrophages interfere with the metabolism of collagen and produce changes in the biomechanics of scars 6,7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of polypropylene-only meshes in direct contact with the viscera and intra-abdominal structures resulted in extensive impairment of visceral adhesions. The use of polypropylene-only meshes for the repair of defects in the abdominal wall and in intimate contact with the intra-abdominal viscera, therefore without any separating films, is associated with the appearance of dense and firm adhesions 21 . Paulo et al .…”
Section: Discussionmentioning
confidence: 99%